Nivolumab for malignant peritoneal mesothelioma. Issue 11 (30th November 2020) - Tanaka, Takaaki; Miyamoto, Yosuke; Sakai, Atsue; Fujimoto, Nobukazu
Abstract : Malignant peritoneal mesothelioma (MPeM) is a highly malignant neoplasm of the peritoneum, which carries a poor prognosis. A 70-year-old man, who was employed in the shipbuilding industry and exposed to asbestos for 50 years, was found to have a low-density lesion in the peritoneum around the liver and spleen, associated with multiple mediastinal and parasternal lymphadenopathy. Laparoscopic exploration was performed, and biopsy specimen analysis led to a diagnosis of MPeM. Initial systemic chemotherapy comprising cisplatin and pemetrexed yielded a modest cytoreductive effect. However, 4 months later, the patient presented with abdominal distension and anorexia. CT images revealed massive ascites, bowel obstruction and an enlarged intra-abdominal tumour, which was considered progression of the MPeM. The patient was treated with nivolumab. Bowel obstruction was improved after the first administration, and his sense of abdomen distension completely disappeared after the third administration. This case supports the utility of immunotherapy in MPeM.